Pemberdayaan Masyarakat untuk Desa Persiapan pada Desa Batu Asaq melalui Pelatihan dan Pendampingan Berbasis Participatory Rural Appraisal - Zainudin Abdussamad; Abdul Muhid; Syamsurrijal Syamsurrijal; Sutarman Sutarman (LPPM Universitas Bumigora, 2022)
The community service which was done to the community in the Batu Asak village aims at helping the community to improve the skill in providing the jajanan Lokal hygienically, attractive packing model, and marketing management. This village is a new village that requires many supports including human resources to establish a skilled community in the future. The service program was done for three months starting from September to November in 2021. to complete this program, the team passes some phases, namely; planning, coordinating, socializing, training, and mentoring. the method used is Participatory Rural Appraisal (PRA) the activity was done through training and mentoring to maintain the skill of the community in producing jajan Lokal hygienically. The result shows that the communities are able to provide the jajanan lokal hygienically, the products have been packed accompanied with the label. Hence, in the future, the team expects much support from University, people and government, in order, the lecturers can do more collaboration.